Seeing Margaret Mitchell’s Gone With the Wind with Fresh Eyes - Emmeline Gros (Transatlantica)
By examining the ways in which Margaret Mitchell’s novel Gone With the Wind (and the character of Scarlett O’Hara specifically) contests heteronormative, patriarchal, masculine constructions of Southern (ideal) femininity, this essay argues that Scarlett’s “ugliness” forces us to widen our perspective on Southern feminine beauty and purity and contributes to challenging the tropes of white Southern masculinity and femininity. The presentation of Scarlett is worthy of note because of the way it demonstrates the terrains of feminine difference and ugliness as complex (and enduring) fields for discussion.